THE BASIC PILLARS OF BUILDING FINANCIAL INCLUSION AND ITS ROLE IN ACHIEVING SUSTAINABLE DEVELOPMENT - Prof. Faril Mushraf Edan; Lect.Dr.Jabbar Saadoon Darag; Assiciate professor Dr.Sahar Fathallah Muhammed Ali; Prof.Dr.Mohammed Abed Salih; Assiciate professor Dr.Wafaa Salah (Scholar Express Journals, 2024)
This research about the topic of financial inclusion, its components, importance, purpose, and the tasks it achieves in sustainable development, in light of the multiple services that are linked to the banking and financial sector in today’s world (financial and banking technologies), as it aims to accelerate access to banking and financial services. Technology and modern financial technologies are the important factor in changing the environment of the financial sector, and in accelerating the adoption of financial inclusion, and countries have become required to achieve financial inclusion, which benefits individuals and banks to quickly access financial and banking services that meet their needs, and which are covered by the banking sector, from: payments and savings. Credit facilities, loans, or any other service. Initiating sustainable development requires a banking sector that can meet development needs, and financial inclusion services must interact positively with development strategies, in an appropriate and responsible manner. Otherwise, the development sector will suffer from: a lack of harmony in the relationship with the banking sector.
Keywords: Financial inclusion; development; sustainable development